Development of Physics Modules with Science, Environment, Technology, and Society (SETS) Approaches to Motion and Force Material - Angelia, Anggi; Muminov, Sarvar Q.; Obafemi, Deborah TA (Cahaya Ilmu Cendekia Publisher, 2023)
Purpose of the study: The goal to be achieved in this research is to produce a physics module with an approach (SETS) on motion and force material with valid, practical, and effective product quality. Methodology: This study uses Research and Development (R&D) development research, with a 4D development model developed by Thiagarajan Semmel and Semmel. This model consists of 4 stages of development, namely define, design, develop, disseminate, or adapted into a 4-P model, namely definition, planning, development, and deployment. The instruments used in this study were validity questionnaires, practicality questionnaires, and effectiveness questionnaires, which were analyzed using a Likert scale. The validity test includes the validity of a questionnaire by 3 lecturers. Furthermore, for the physics module with the validity SETS approach by 5 lecturers at UIN Imam Bonjol Padang. The practicality test of the physics module with the SETS approach can be seen from the practicality questionnaire sheet by 2 science educators and 29 class VIII students at Junior High School 1 Tigo Nagari. The effectiveness test included the effectiveness of the students' reading interest questionnaire on the physics module with the SETS approach which was completed by 32 class VIIIg students at Junior High School 1 Tigo Nagari. Main Findings: The result of this research is to produce physics modules with the SETS approach with valid, practical and effective product quality. The results of the validation of the physics module with the SETS approach in the material aspects by 2 validators obtained 81 results with very valid categories, the results of media validation by 2 validators were 98.88 with very valid categories, the results of language validation by 1 validator were 92 with very valid criteria, based on the three aspects of validity, the results of product validity are obtained, namely with very valid criteria. The results of product practicality by 2 educators were 97.14 with very practical criteria. The result of practicality by 29 class VIIIb students was 92.6 with very practical criteria. The test results for the effectiveness of use by 32 class VIIIg students were 91.24 with very effective criteria. It can be concluded that the physics module with the SETS approach to motion and force material for class VIII students meets the valid, practical, and effective criteria. Novelty/Originality of this study: produce physics modules with Approach (SETS) on motion and force material with valid, practical, and effective product quality.